2017
DOI: 10.1080/00365513.2017.1354255
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic factors and oxidative stress in osteoarthritis: a case–control study

Abstract: Previous studies suggest that metabolic disturbances might be involved in the development of osteoarthritis (OA). Associations have been found between the individual components of metabolic syndrome (MetS) and OA. MetS has been associated with increased oxidative stress (OxS). The study aimed to clarify the role of MetS components in OA and to evaluate the levels of OxS in OA patients and in age-matched controls. Fifty-five patients with end-stage OA (age 63 ± 7 years) prior to hip or knee joint replacement su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 38 publications
1
29
0
2
Order By: Relevance
“…Evidence from previous studies indicated that oxidative stress may have a critical role in the pathophysiology of OA. There are many studies investigating levels of oxidative markers in the blood and the SF samples of OA patients . However, the results are still controversial and it is not fully understood whether SF increases or decreases the status of oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from previous studies indicated that oxidative stress may have a critical role in the pathophysiology of OA. There are many studies investigating levels of oxidative markers in the blood and the SF samples of OA patients . However, the results are still controversial and it is not fully understood whether SF increases or decreases the status of oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies investigating levels of oxidative markers in the blood and the SF samples of OA patients. 32,34,35 However, the results are still controversial and it is not fully understood whether SF increases or decreases the status of oxidative stress. 36,37 Moreover, it is difficult to discriminate the difference among the statuses of oxidative stress in different stages of knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…ox-LDL and oxidative stress parameters were reported to be higher in KOA patients and correlated with KOA severity 33 . Endstage HOA/KOA patients have increased levels of oxidative stress markers, decreased antioxidant capacity, impaired lipid metabolism, and dysglycemia 34 . Moreover, glycoprotein YKL-40, a potential marker for active inflammatory process, is involved in the pathogenesis of KOA synovitis 35 .…”
Section: Association With Clinical Scores and Changesmentioning
confidence: 99%
“…Существует мнение, что повышение общего холесте-рина, ЛПНП и ТГ в сыворотке крови ассоциировано с развитием и прогрессированием ОА коленных суставов [38][39][40]. В нашем исследовании практически все паци-енты имели дислипидемию.…”
Section: Discussionunclassified